The shape of words in the brain. - Kovic, V; Plunkett, K; Westermann, G (2010)
The principle of arbitrariness in language assumes that there is no intrinsic relationship between linguistic signs and their referents. However, a growing body of sound-symbolism research suggests the existence of some naturally-biased mappings between phonological properties of labels and perceptual properties of their referents (Maurer, Pathman, and Mondloch, 2006). We present new behavioural and neurophysiological evidence for the psychological reality of sound-symbolism. In a categorisation task that captures the processes involved in natural language interpretation, participants were faster to identify novel objects when label-object mappings were sound-symbolic than when they were not. Moreover, early negative EEG-waveforms indicated a sensitivity to sound-symbolic label-object associations (within 200ms of object presentation), highlighting the non-arbitrary relation between the objects and the labels used to name them. This sensitivity to sound-symbolic label-object associations may reflect a more general process of auditory-visual feature integration where properties of auditory stimuli facilitate a mapping to specific visual features.